2017
DOI: 10.1097/scs.0000000000003506
|View full text |Cite
|
Sign up to set email alerts
|

Midfacial Changes Through Anterior Maxillary Distraction Osteogenesis in Patients With Cleft Lip and Palate

Abstract: Maxillary hypoplasia is a major issue in cleft lip and palate patients, and predictable surgical maxillary advancement is required. In the present study, the changes and stability of the maxilla and soft tissue profile achieved after the application of anterior maxillary distraction osteogenesis (AMDO) using intraoral expander in unilateral cleft lip and palate and isolated cleft palate patients were investigated by comparing to the Le Fort I osteotomy (LFI) and maxillary distraction osteogenesis (DO) with rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 17 publications
3
15
0
Order By: Relevance
“…In the current study, the mandible rotated backward and downward without surgical intervention to fit the new position of the maxilla after distraction. These findings are consistent with those of previous studies reporting clockwise rotation of the mandible, [26][27][28] although other studies have reported the absence of significant changes in the sella-nasion-B angle 51,52 or the posterior rotation of the mandible. 53 It may be that the occlusal relationship is altered when the maxilla is displaced.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, the mandible rotated backward and downward without surgical intervention to fit the new position of the maxilla after distraction. These findings are consistent with those of previous studies reporting clockwise rotation of the mandible, [26][27][28] although other studies have reported the absence of significant changes in the sella-nasion-B angle 51,52 or the posterior rotation of the mandible. 53 It may be that the occlusal relationship is altered when the maxilla is displaced.…”
Section: Discussionsupporting
confidence: 93%
“…These findings are consistent with those of other studies. [26][27][28] Furthermore, a 3-dimensional analysis of airway variables and spaces after the movement of the bony structures revealed that 4 out of 5 zones of airway space (ie, nasal cavity, nasopharynx, velopharynx, and upper oropharynx) exhibited significant increases in volume after distraction, whereas no changes were noted in the volume of the lower oropharyngeal airway. The analysis also revealed a correlation between airway variables and the horizontal advancement of the maxilla.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, conventional facemask therapy used between the mixed dentition and the end of adolescent growth is not always the best treatment for patients with skeletal crossbite. If the degree of skeletal malocclusion is severe, then surgical procedures such as Le Fort I osteotomy or anterior maxillary distraction osteogenesis 7 are useful to correct the skeletal disharmony after completion of adolescent growth. In recent years, the number of cases showing marked growth suppression of the maxilla has decreased because of surgical technique improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have attempted to evaluate the facial soft tissue changes following OGS or DO and determine the correlations and ratios of soft-to-hard tissue changes in cleft lip and palate (CL/P) patients 8–19 . However, the facial soft tissues of CL/P patients differ from those of noncleft normal patients morphologically and behaviorally owing to the cleft-related deformity itself and scar tissues in the lip, nose, and alveolus 20,21 …”
mentioning
confidence: 99%